Правове регулювання юридичної відповідальності суб’єктів трудового права в умовах ринкової економіки : автореф. дис. - Дуравкіна, Н. І.; Duravkina, N. I.; Дуравкина, Н. И.; ORCID: http://orcid.org/0000-0002-5075-9109 (Луганськ, 2011)
У дисертації розкривається поняття «соціально-правовий механізм забезпечення прав людини», визначається розвиток наукової думки щодо понять «відповідальність» та «юридична відповідальність» взагалі, та в трудовому праві зокрема. Досліджується роль і функції відповідальності в механізмі забезпечення прав і свобод людини та громадянина. Виділяються сигналізаційна (інформативна) та організуюча (регулятивна) функції юридичної відповідальності. Змістом першої є визначення моделі поведінки, що суперечить інтересам суспільства й держави та характеризується як протиправна. Змістом другої є забезпечення регулювання суспільних відносин шляхом запобігання правопорушенням, покарання винних у їх скоєнні осіб і відновлення порушених прав та законних інтересів людини й громадянина.

The thesis is devoted to the complex analysis of the role and functions of responsibility in the mechanism of human rights and freedoms provision. The signaling (informative) and organizing (regulative) functions of legal responsibility are pointed out. The essence of informative function is to determine the behavioral model inconsistent with social and state interests which is characterized as illegal. The essence of regulative function is to secure regulation of social relations by means of offence prevention, punish the guilty persons and restore their violated rights and legal interests. The author defines the notion of ‘social and legal mechanism of securing human rights’, outlines the scientific origin of such notions as ‘responsibility’, and ‘legal responsibility’ in general and in labour law meanings. The notion of ‘responsibility’ in labour law and conditions of its attachment are formulated, the historical development of the institute of responsibility in labour law, its types and classification are outlined. The generation of scientific idea concerning disciplinary and financial responsibility of employer and employee, grounds and conditions of its imposing are studied. Formation of a separate institute of employee’s labour rights protection is substantiated, the place of this institute in labour law is defined. The issue of compensation the moral damage, suffered while officiating, got its further development, the legal solution of this problem was proposed.

В диссертации уточняется понятие «социально-правовой механизм обеспечения прав человека», определяется развитие научной мысли относительно понятий «ответственность» и «юридическая ответственность» в целом, и в трудовом праве в частности. Исследуются роль и функции юридической ответственности в механизме обеспечения прав и свобод человека и гражданина. Выделены сигнальная (информативная) и организационная (регулятивная) функции юридической ответственности. Содержанием первой является определение модели поведения, которая противоречит интересам общества и государства и характеризуется в качестве противоправной. Содержанием второй является обеспечение регулирования общественных отношений путем предотвращения правонарушений, наказания виновных в их совершении лиц и возобновления нарушенных прав и законных интересов человека и гражданина.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Legal Securing of Keeping the Requirements of Labour Legislation by Means of Determining Responsibility
Дуравкіна, Н. І. Правове регулювання юридичної відповідальності суб’єктів трудового права в умовах ринкової економіки : автореф. дис. ... канд. юрид. наук : 12.00.05 / Н. І. Дуравкіна; Східноукр. нац. ун-т ім. В. Даля. - Луганськ, 2011. - 19 с.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.05; відповідальність; юридична відповідальність; дисциплінарна відповідальність; матеріальна відповідальність; роботодавець; працівник; моральна шкода; responsibility; legal responsibility; disciplinary responsibility; financial responsibility; employer; employee; moral damage; ответственность; юридическая ответственность; дисциплинарная ответственность; материальная ответственность; работодатель; работник; моральный ущерб